Fueling conflict? (De)escalation and bilateral aid - Richard Bluhm; Martin Gassebner; Sarah Langlotz; Paul Schaudt (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2016)
This paper studies the effects of bilateral foreign aid on conflict escalation and de-escalation. We make three major contributions. First, we combine data on civil wars with data on low level conflicts in a new ordinal measure capturing the two-sided and multifaceted nature of conflict. Second, we develop a novel empirical framework. We propose a dynamic ordered probit estimator that allows for unobserved heterogeneity and corrects for endogeneity. Third, we identify the causal effect of foreign aid on conflict by predicting bilateral aid flows based on electoral outcomes of donor countries that are exogenous to recipients. We establish that the effect of foreign aid on the various transition probabilities is heterogeneous and can be substantial. Receiving bilateral aid raises the chances of escalating from small conflict to armed conflict, but we find no evidence that aid ignites conflict in truly peaceful countries.
Keywords: D74; F35; O11 : C25; 330; conflict; foreign aid; political economy; dynamic ordered panel data